HUBUNGAN ASUPAN KONSUMSI MAKANAN BERMINYAK, MANIS DAN ASIN DENGAN INDEKS MASSA TUBUH (IMT) - Istarofah, Lisa; Fatimatuzzahro, Maulinda; Ningrum, Arni Fitriya; Aprillyana, Halima; Lestari, Catur Retno (Indonesian Journal of Nutrition Science and Food; Vol 2 No 2 (2023): Januari 2023, 2023)
Body mass index (BMI) is a simple index of body weight to body weight used to classify overweight and obesity in adults. Body mass index (BMI) is defined as a person's body weight in a kilogram divided by squares of height in meters (kg/m2). The purpose of this study is to determine the relationship of consumption of oily, sweet and salty foods with IMT and determine their classification. This research is quantitative applying descriptive analysis with a cross sectional approach. The instruments used in the form of digital scales, microtoise, informed consent, Food Recall Food Recall 3 times 24 hours and Semi-Food Frequency Questionnaire SQ-FFQ quantitative questionnaire. The population of this study was all scope of university Ivet with a total of 120 universitas Ivet students. The sample of this study amounted to 30. In this study it can be concluded that between IMT and fat, iodine, sugar is not related to the food recall questionnaire 3 times 24 hours or a semi -quantitative food frequency questionnaire SQFFQ.